Methadone Maintenance Treatment Versus Methadone Maintenance Treatment Plus Auricular Acupuncture: Impacts on Patient Satisfaction and Coping Mechanism. (December 2013) - Lua, Pei Lin; Talib, Nor Samira; Ismail, Zabidah
This study intended to (1) describe the baseline patient satisfaction level and preferred coping strategies and (2) assess patient satisfaction and coping mechanisms pre- and postintervention. Patients on methadone maintenance treatment (MMT) in Terengganu, Malaysia, were randomized into either MMT or MMT plus auricular acupuncture (MMT + AA) groups. All received the standard MMT, while participants on MMT + AA underwent concurrent AA session thrice weekly for 2 months (each session = 30 minutes). Data analysis was carried out using SPSS 16.0, employing descriptive and nonparametric statistics. Participations were received from 97 eligible male patients (median age = 36.0 years; Malay = 97.9%). After screening for dropouts, only 69 patients were considered for subsequent analysis (MMT = 40; MMT + AA = 29). At preintervention, both groups did not differ significantly in the parameters investigated. During postintervention, no significant difference was detected for satisfaction level but coping-wise, substance use was significantly and frequently adopted by MMT + AA patients compared to MMT respondents ( P < .05). On separate analysis, those who received MMT alone adopted active coping, venting, and self-blame significantly more frequently postintervention ( P < .05). Nevertheless, no significant difference for coping styles of MMT + AA patients was exhibited over time ( P >.05). The addition of AA therapy into the standard MMT treatment did not seem to influence patient satisfaction and their coping ways.